2020
DOI: 10.1186/s12960-020-00469-9
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in nursing: a theoretical review

Abstract: Background: Workforce studies often identify burnout as a nursing 'outcome'. Yet, burnout itself-what constitutes it, what factors contribute to its development, and what the wider consequences are for individuals, organisations, or their patients-is rarely made explicit. We aimed to provide a comprehensive summary of research that examines theorised relationships between burnout and other variables, in order to determine what is known (and not known) about the causes and consequences of burnout in nursing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
608
4
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(661 citation statements)
references
References 114 publications
(279 reference statements)
27
608
4
22
Order By: Relevance
“…Though the relationship between RT leadership and burnout has not been specifically studied, studies of physicians and nurses have found leadership behaviors significantly impact burnout and well-being. [14][15][16] Nursing studies indicate that low support from leadership, inauthentic leadership, and negative team relationships are associated with burnout. 16 The first step in combating burnout within RT departments is to accurately measure burnout rates and identify key drivers in individual centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the relationship between RT leadership and burnout has not been specifically studied, studies of physicians and nurses have found leadership behaviors significantly impact burnout and well-being. [14][15][16] Nursing studies indicate that low support from leadership, inauthentic leadership, and negative team relationships are associated with burnout. 16 The first step in combating burnout within RT departments is to accurately measure burnout rates and identify key drivers in individual centers.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Nursing studies indicate that low support from leadership, inauthentic leadership, and negative team relationships are associated with burnout. 16 The first step in combating burnout within RT departments is to accurately measure burnout rates and identify key drivers in individual centers. RT leaders could then use these data to focus on specific leadership behaviors as a strategy to combat burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout is characterized by emotional exhaustion, cynicism, and depersonalization due to chronic exposure to workplace stressors and lack of emotional resources and supports ( 5 ). A recent review of 91 empirical studies on nurse burnout found significant associations between burnout and intent to leave, sickness absence, decreased job performance, and decreased perceived general health ( 6 ). Nurse burnout can occur as a result of moral distress and is identified in the literature as negatively impacting interprofessional teamwork and contributing to nurse attrition ( 6 , 7 ).…”
mentioning
confidence: 99%
“…A recent review of 91 empirical studies on nurse burnout found significant associations between burnout and intent to leave, sickness absence, decreased job performance, and decreased perceived general health ( 6 ). Nurse burnout can occur as a result of moral distress and is identified in the literature as negatively impacting interprofessional teamwork and contributing to nurse attrition ( 6 , 7 ). Further, moral distress is linked to poor collaboration with physicians, thereby jeopardizing the quality of decision making in the ICU environment ( 7 , 8 ).…”
mentioning
confidence: 99%